Pengaruh Budaya Organisasi, Kepemimpinan Demokratis, dan Konflik, terhadap Kinerja Karyawan Phia Deva Yogyakarta - Ayu Anisa; Tasrim Tasrim; Damiasih Damiasih (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the influence of organizational culture, democratic leadership, and conflict on employee performance at Phia Deva Yogyakarta. The research employs a quantitative approach using survey methods and questionnaires as data collection instruments. The sample used in this study is a saturated sample consisting of 30 respondents, representing the total number of employees. Data analysis was conducted using simple and multiple regression techniques to assess the influence of independent variables on the dependent variable. The method employed is quantitative survey research. The results of the F-test indicate that organizational culture, democratic leadership style, and conflict simultaneously have a significant positive influence on employee performance at Phia Deva Yogyakarta. The significance value (F statistic) of 0.000 is smaller than the significance level of 0.05, and the F statistic value is greater than the F table value (35.527 > 2.91). This demonstrates that organizational culture, democratic leadership style, and conflict collectively have a significant positive effect on employee performance at Phia Deva Yogyakarta. The results of the determination coefficient test (R2) or R Square are 0.804 or 80.4%, indicating that organizational culture (X1), democratic leadership (X2), and conflict (X3) collectively explain 80.4% of the variability in employee performance (Y), while the remaining 19.6% is influenced by other variables not included in this study.